Kriteria Seleksi Masuk Fakultas Kedokteran sebagai Prediktor Presentasi Akademik - Dedeh Supantini; Lusiana Darsono; Winsa Husin (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Selection of students into medical school should have two distinct purposes: to enroll students that most likely to succeed in their academic and clinical year, and subsequently become competent and professional medical practitioner. Numbers of applicants and numbers of students accepted in Faculty of Medicine of Maranatha Christian University (MCU) was tend to increase each year. The selection of medical students was based on General Admission Test (GAT) prepared by admission committees of MCU. To improve the selection procedure, since 2009, the Faculty developed Medical Faculty Admission Test (MFAT) as additional selection tool to assess cognitive attributes in basic biomedical sciences. The objective of this study was to evaluate how well the selection criteria predict academic performance, and to identify if there were any aspects of prior academic history and student’s characteristic that correlate with subsequent students performance during medical program.Method: We studied students cohort of the 2009. Selection criteria were GAT and MFAT. Prior academic performance explained by student’s score on National High School Examination (NHSE) and student’s score on biology. Academic performance was defined as cumulative first year Grade Point Average (GPA). Correlation between GPA and selection criteria or student’s characteristic was calculated using Pearson’s correlation coefficient. Multiple regressions was performed for each outcome variable with all variables included. Statistical significance was set at p < 0,05Results: There were 167 students included in this study. Bivariate correlation analysis with Pearson’s correlation showed that MFAT (= 0,354,p<0,01) and GAT ( r=0,301, p<0,01) were correlated with student’s academic performance. The results of multivariate analysis with multiple regression showed that MFAT and GAT are predictors of first year academic performance defined by GPA (R multiple = 0,404, p<0,001).Conclusion: Medical Faculty of MCU selection criteria ere correlated with academic performance.